Farelo de algodão em rações para suínos nas fases de crescimento e terminação - Mello, G. [UNESP]; Laurentiz, A. C. [UNESP]; Filardi, R. S. [UNESP]; Bergamaschine, A. F. [UNESP]; Okuda, H. T. [UNESP]; Lima, M. M. [UNESP]; Junqueira, O. M. [UNESP] (SciELO Espana/Repisalud, 2012)
Forty-eight pigs with 63 day olds and average weight of 23.40±1.3 kg, were allotted in a randomized block design with three treatments(0%, 10% and 20% of cottonseed meal (FA) in diets) and eight replicates with two pigs (one barrow and one gilt). The blocks were used to control changes in initial body weight. Experimental period was the growth phase (63 to 106 days old) and growing-finishing (63 to 147 days old). In each phase the diets were isonutritives, varying however the levels of crude fiber. The levels of cottonseed meal (FA) did not affect (p>0.05) the performance of animals during the growth phase or during the total period of evaluation (growingfinishing). The qualitative parameters of manure indicated that the FA determined decrease in the nitrogen and phosphorus content, but only in the growth phase. In the finishing phase the increase in the FA inclusion promoted an increase in dry matter content. Although FA can be used in up to 20% in diets for pigs in the growing and finishing phase, it is necessary to include L-lysine and soybean oil which causes an increase in cost per kg produced pig.
Cottonseed meal in diets for growing and finishing pigs
Keywords: Alternative feed; Economic analysis; Swine manure; Animalia; Glycine max; Micropus; Suidae